Secret frequencies : a New York education - Skoyles, John (American lives., 2003)
"In his memoir, John Skoyles guides us through 1960s New York, a city we only thought we knew. Against a backdrop of late-night radio airwaves featuring talk-show kings like Long John Nebel, the sixteen-year-old pairs up with his Uncle Fred, a Mob associated and man-about-town who presses him into the seamy underworld of con games and call girls. At the same time, his Aunt Linda finds him a job as a messenger at Paramount Pictures on Times Square, where she works as a secretary and where Michael Caine and Jane Fonda make cameo appearances." "From the bars and swank apartments of Manhattan's Upper East Side to 42nd Street flophouses and haunts like Hubert's Freak Show, Skoyles comes face to face with New York's most comic, absurd, and sometimes dangerous seductions."